The effect of baseline versus early glucocorticoid use on immune checkpoint inhibitor efficacy in patients with advanced NSCLC - Wang, Yifan; Zhou, Jianying; Peng, Simin; Cui, Zhao; Wang, Weiqi; Zeng, Wenqin; Qiu, Tingting; Liu, Zhentian (Frontiers in Oncology, 2025)
PurposeThis study aims to investigate the specific effects of glucocorticoids (GC) on the efficacy of immune checkpoint inhibitors (ICIs), and whether this effect is influenced by the timing and dosage of GC administration. Changes in the neutrophil percentage and the helper/suppressor T lymphocyte ratio [NEUT %/(CD4+/CD8+)] during GC administration were monitored.MethodsThe clinical results of 130 patients with advanced non-small cell lung cancer (NSCLC) treated with ICIs were analyzed and compared with those of patients who did not use GC. Cox proportional hazards regression model and Logistic regression analysis were used to analyze the factors affecting ORR and PFS, and t test was used to analyze the changes of NEUT %/(CD4 +/CD8 +) during GC use.ResultsMultivariate Logistic analysis showed that GC use was associated with a higher ORR in 130 patients treated with ICIs [HR = 3.07,95% CI (1.31-7.21), P = 0.010]. Univariate Cox analysis showed that GC use was not significantly correlated with PFS [HR = 0.926,95% CI (0.603-1.420), P = 0.710]. Patients who used GC during the baseline period of ICIs treatment had a higher ORR than those who used GC at the early stage of ICIs treatment (65.4% vs 30.8%, p = 0.024). Multivariate Cox analysis showed that GC use had longer PFS [HR = 0.37,95% CI (0.17-0.78), p = 0.009]. The timing of GC use was different, and there was a difference in NEUT %/(CD4 +/CD8 +) levels before and after treatment. There was no significant difference in ORR and PFS between GC duration and dose.ConclusionThe use of GC helps to enhance the efficacy of immunotherapy. In particular, GC use during the baseline period leads to higher ORR and PFS, regardless of the dose or duration of GC use. The levels of NEUT %/(CD4+/CD8+) varied depending on the timing of GC administration.